2017
DOI: 10.1186/s12886-017-0484-5
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine screening of retinal diseases with a handheld portable non-mydriatic fundus camera

Abstract: BackgroundWe modified and reconstructed a high image quality portable non-mydriatic fundus camera and compared it with the tabletop fundus camera to evaluate the efficacy of the new camera in detecting retinal diseases.MethodsWe designed and built a novel portable handheld fundus camera with telemedicine system. The image quality of fundus cameras was compared to that of existing commercial tabletop cameras by taking photographs of 364 eyes from the 254 patients. In all 800 fundus images taken by two camera ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 20 publications
(25 reference statements)
1
41
0
Order By: Relevance
“…A study conducted in USA 86-94% images were gradable before pupil dilatation in hand-held retinal imaging [47]. Similarly a study conducted in a upper middle income setting (China) reported a low ungradable proportion of 4.75% (19/400) using a hand-held camera [21]. The low prevalence of DR in our study could be attributed to many factors.…”
Section: Participants' Characteristicssupporting
confidence: 48%
“…A study conducted in USA 86-94% images were gradable before pupil dilatation in hand-held retinal imaging [47]. Similarly a study conducted in a upper middle income setting (China) reported a low ungradable proportion of 4.75% (19/400) using a hand-held camera [21]. The low prevalence of DR in our study could be attributed to many factors.…”
Section: Participants' Characteristicssupporting
confidence: 48%
“…Jin et al . constructed their own portable non‐mydriatic fundus camera and compared it to a traditional, table‐top fundus camera . The image quality was graded for both devices, with similar levels between the two methods, and similar ability to detect fundus findings.…”
Section: Newer Alternatives To Fundus Camerasmentioning
confidence: 99%
“…Some defined the cup margin at specific depths from the disc margin such as 150 and 120 μm. Others defined the margin as a proportion of the total cup depth such as one‐fifth, one‐third and one‐half . One group used a hybrid approach defining the cup margins as 150 μm depth while using one‐fifth depth for especially shallow or deep cups (<0.2 or >1.0 mm) .…”
Section: Alternatives To Optic Nerve Analysis By Physiciansmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of portable fundus imaging systems has enabled greater access to disease screening, monitoring, and documentation in resource-poor situations and reduced the level of expertise required for the user. 1 Handheld fundus cameras such as the Optomed line of systems have shown good clinical value in several diseases in comparison to traditional desktop fundus cameras in clinics. 2,3 However, these systems cost approximately $10 000 to $14 000 each and require dedicated electronics, limiting their reach.…”
mentioning
confidence: 99%